2012
DOI: 10.1038/ejcn.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

INSIG2 variants, dietary patterns and metabolic risk in Samoa

Abstract: Background/Objectives Association of insulin-induced gene 2 (INSIG2) variants with obesity has been confirmed in several but not all follow-up studies. Differences in environmental factors across populations may mask some genetic associations and therefore gene-environment interactions should be explored. We hypothesized that the association between dietary patterns and components of the metabolic syndrome could be modified by INSIG2 variants. Subjects/Methods We conducted a longitudinal study of adiposity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
3
19
2
Order By: Relevance
“…Environmental factors that distinguish higher vs. lower triglycerides (e.g., obesity, physical inactivity, smoking, alcohol, high-carbohydrate diets, T2DM) are predicted to produce different genetic estimates under quantile-dependent expressivity. Traditionally, these differences have been attributed to gene-environment interactions, where: 1) the effect of the genotype on the phenotype differs by environment [26][27][28][29][30][31][32][33][34][35][36][37][41][42][43][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][65][66][67][74][75][76][77][78][79][80] , or equivalently: 2) the effect of the environment on the phenotype differs by genotype 36,[38][39][40]44,…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors that distinguish higher vs. lower triglycerides (e.g., obesity, physical inactivity, smoking, alcohol, high-carbohydrate diets, T2DM) are predicted to produce different genetic estimates under quantile-dependent expressivity. Traditionally, these differences have been attributed to gene-environment interactions, where: 1) the effect of the genotype on the phenotype differs by environment [26][27][28][29][30][31][32][33][34][35][36][37][41][42][43][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][65][66][67][74][75][76][77][78][79][80] , or equivalently: 2) the effect of the environment on the phenotype differs by genotype 36,[38][39][40]44,…”
Section: Discussionmentioning
confidence: 99%
“…The WDP increases diabetes risk, especially among those with an increased genetic susceptibility to this disease [38]. Samoans adhering to the modern pattern characterized by a high intake of processed foods had higher TG if they were homozygous for the rs9308762 C allele [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The gene-diet interaction has helped to shed more light on an understanding of this variability, an area that has been poorly explored [6,13]. Baylin et al [14] reported that Samoans adhering to modern dietary patterns have high TG levels if they are homozygous for the rs9308762 C allele. In both Japanese and Chinese Malaysian subjects, significant interactions were found between selected dietary patterns and VEGFR2 single nucleotide polymorphisms (SNP) and blood lipids [15].…”
Section: Introductionmentioning
confidence: 99%
“…While modernization and consequent changes in lifestyle patterns are clearly associated with the increase in adiposity and abnormalities in cardiometabolic traits, there is strong evidence from numerous studies that genetic factors influence our response to environmental exposures such as changing lifestyle and diet (Bouchard, ; Qi and Cho, ). Our prior research in Samoans showed that genetic variation is associated with adiposity and cardiometabolic risk factors (Åberg et al, ) as well as modulation of those risks by gene–environment interaction (Baylin et al, ). Precise identification of loci involved in these complex traits has, however, been difficult, with candidate gene and family‐based linkage studies having limited success.…”
mentioning
confidence: 99%